Peterson's graduate programs in business, education, health, information studies, law & social work. - Peterson's Guides, Inc. (Princeton, N.J. Peterson's, 1997)
Annual
"Book 6.".
Continues: Peterson's guide to graduate programs in business, education, health, and law.
Running title: Peterson's guide to graduate programs in business, education, health, information studies, law and social work.
Keywords: Business education -- United States -- Directories; Commerce -- Education -- United States -- directories; Education -- Graduate work -- United States -- Directories; Education, Graduate -- United States -- directories; Health occupations schools -- United States -- Directories; Information Science -- Education -- United States -- directories; Information science -- Study and teaching (Graduate) -- United States -- Directories; Law -- Study and teaching (Graduate) -- United States -- Directories; Schools, Health Occupations -- United States -- directories; Social work education -- United States -- Directories; Social Work -- Education -- United States -- directories; Universities -- United States -- directories